Employing RSM to model thermal performance and exergy destruction of LS-3 parabolic trough collector by coupling MCRT and CFD techniques - Rajhi, Wajdi; Mehryan, S. A. M.; Elbashir, Nasrin B. M.; Aybar, Hikmet S.; Aich, Walid; Eladeb, Aboulbaba; Kolsi, Lioua (Elsevier, 2024)
This study investigates the thermal performance and exergy destruction of parabolic trough collector by Response Surface Methodology. This collector is simulated by the Monte Carol Ray Tracing method and the results are coupled to the Computational Fluid Dynamics. Thermohydraulic performance and the characteristics of the thermodynamics second law are studied with the turbulence-inducing elements and hybrid nanofluid. The absorber tube features elements with a helical profile along its wall. New correlations are presented to describe thermal performance and exergy destruction, and the modeling output shows that these correlations have high prediction accuracy. Response Surface Methodology results also show that turbulators have a nonlinear effect on thermal performance while the Reynolds number has a nonlinear effect on exergy destruction. Fe 3 O 4 nanoparticles and carbon nanotube lead to an increase of 13 % and 10 % of Nusselt number, respectively, at Re = 12000. Also, it leads to a decrease of 7 % and 6.7 % of exergy destruction, respectively. Increasing the working fluid flow rate from 12000 to 22000 improves thermal performance up to 73 %, and decreases exergy destruction up to 48 %. The maximum value of thermal performance is equal to 2.1, and this value is related to the highest Reynolds number and the absorber tube including turbulence-inducing elements.
Keywords: Response surface methodology; Monte Carol ray tracing; Parabolic trough collector; Exergy destruction; Hybrid nanofluid